Cross-Border Data Sharing and Sovereignty: Reactions of Non-EU Countries to Article 32 of the Budapest Convention - Gabriela I. Matei (Law and Economy, 2024)
This paper examines the concerns of non-EU countries regarding Article 32 of the Budapest Convention on Cybercrime, which allows cross-border access to stored computer data under certain conditions. While Article 32 aims to enhance international cooperation in combating cybercrime, it has been met with resistance from several non-EU countries due to perceived threats to national sovereignty, conflicts with domestic data protection laws, and concerns over fairness and equity in its application. The paper explores these concerns in detail, highlighting the potential impacts on data privacy, legal autonomy, and international cooperation. It discusses the broader implications of these reactions for global cybersecurity efforts, including the erosion of trust, fragmentation of international frameworks, and challenges to harmonizing cybercrime laws. The paper argues for a more balanced and inclusive approach to cross-border data sharing that respects diverse legal traditions and promotes greater transparency, dialogue, and mutual trust among nations. Addressing these concerns is crucial for ensuring that the Budapest Convention remains an effective tool for combating cybercrime in a way that is fair, equitable, and respectful of all countries’ interests.